Estimating Safely Managed Sanitation in Urban Areas; Lessons Learned From a Global Implementation of Excreta-Flow Diagrams - Peal, Andy; Evans, Barbara; Ahilan, Sangaralingam; Ban, Radu; Blackett, Isabel; Hawkins, Peter; Schoebitz, Lars; Scott, Rebecca; Sleigh, Andy; Strande, Linda; Veses, Oscar (Frontiers in Environmental Science, 2020)
The urban population will rise to 6.7 billion by 2050. The United Nations has committed to provide everyone with safely managed sanitation, but there is limited understanding of the scale of the challenge. This paper describes a methodology for rapid assessment of sanitation in cities including a graphical representation (a shit-flow diagram or SFD) and reports on findings from implementation in 39 cities. The SFD provides high level information for planning purposes covering the entire sanitation system in a city. More than half of the human excreta produced in these cities is not safely managed. The most significant portions of the unsafely managed excreta are: (i) contents of pits and tanks which are not emptied and are overflowing, leaking, or discharging to the surrounding environment (14 per cent); (ii) contents of pits and tanks which are emptied but not delivered to treatment (18 per cent); (iii) faecal sludge and supernatant delivered to treatment but not treated (3 per cent); (iv) wastewater in sewers not delivered to treatment (14 per cent); and (v) wastewater delivered to treatment but not treated (6 per cent). Many cities currently relying on onsite sanitation for safe storage, particularly in Africa, will need new strategies as populations grow. Containment systems that discharge to open drains are common in some Asian cities; these pose a public health risk. Dumping of excreta is widespread and there is a lack of realistic performance data on which estimates of the extent and effectiveness of treatment can be made. The SFD production process can be challenging due to a lack of data and low technical capacity in cities. There is often uncertainty over terminology and over the status of infrastructure. Formalizing definitions for the SFD preparation process was found to be useful in overcoming capacity constraints in cities. The SFD produces a credible snapshot of the sanitation situation in a city. The paper provides evidence of the urgent need for improved management and monitoring of urban sanitation in cities around the world and highlights the role of the SFD as a planning tool.